Investigation of the constitutive relationship between energy damage and CFRP layers in axially compressed small coal cylinders: Experiment and simulation - Qingwen Li; Chuangchuang Pan; Yuqi Zhong; Wenxia Li; Mengjiao Xu; Lei Zhang; Shuaishuai Zhang (Polymer Testing)
This study investigates the effect of CFRP layer count on the mechanical properties and energy evolution of axially compressed small coal cylinders using uniaxial compression tests and FDM-DEM coupled simulations. The experimental and simulation results exhibit excellent agreement, with the error range is controlled within 10 %. This consistency effectively validates the reliability of the research methodology employed. Results show that both unconfined and CFRP-confined small coal cylinders exhibit four stress-strain stages: compaction, elasticity, yielding, and post-peak. CFRP confinement significantly enhances the ductility, with peak stress, peak strain, and elastic modulus increasing by approximately 200 %, 250 %, and 100 %, respectively. Numerical simulations reveal that increasing CFRP layers raises peak stress by 548 % and peak strain by 733 %, with energy absorption efficiency improving by up to 1051 %. However, elastic modulus does not increase monotonically, suggesting a trade-off between strength and stiffness in design. Additionally, CFRP confinement alters the failure mechanism from shear-tensile combined failure to shear failure, with crack distribution becoming more concentrated. Energy and acoustic emission analysis show that CFRP layers enhance energy dissipation, delay crack propagation, and improve residual bearing capacity. Based on these findings, an energy dissipation damage ontology model for small coal cylinders confined by CFRP layers is proposed, providing a useful tool for both theoretical research and engineering practice.